Child and adolescent sexual abuse: perception of healthcare professionals in Nigeria - Ogunjimi, Adetola Ibiwumi (2019)
Sexual experiences of Nigerian Children and adolescents remain underrepresented in both professional practices and academic literatures despite international initiatives and policies against sexual violence. Thousands of Nigerian children have been subjected to sexual violence and discrimination yearly within the family and social settings, and their human rights as citizens have been cruelly disrespected. This understanding thus points to the need to analyze theoretical frameworks that can lead to understanding this phenomenon within today\'s specifics and its different forms of manifestation, and finally the recognition of the existing link between violence, it\'s social and cultural aspects of a given society. To solve and prevent this problem, it is necessary to understand vulnerability factors (individual and collective factors) influencing the occurrence of sexual abuse among Nigerian children and adolescents, and its consequences. The aim of this study was to understand the perceptions that healthcare professionals\' attribute to child and adolescent sexual abuse and its consequences as experienced by their clients in Nigeria. The study is a qualitative study carried out in Lagos State University Teaching Hospital (LUTH) in Lagos State, Nigeria. The group of participants consisted of 14 healthcare professionals working with sexually abused children and adolescents in Nigeria including Medical Doctors, Nurses and Psychologists, between ages 22 and 50 years old. Data was collected through a semi-structured interview. The analysis was performed by means of thematic content analysis using CAQDAC resource, Atlas.ti 8. The result presented six thematic Nuclei: (1) The child victim of sexual abuse and their individual vulnerability, (2) Sexual abuse and its relation to the perpetrator, (3) Intrafamily vulnerabilities and sexually abused victims, (4) Indissociability between sexual abuse and socio-economic vulnerability factors, (5) Sexual abuse and the programmatic structures and lastly, (6) Sexually abused victims and immediate, shortterm and long-term sufferings. The study shows the complexity of child and adolescent sexual abuse occurrences and argues that all factors are significantly important in understanding the health issue. In conclusion, to positively improve the health conditions of children and adolescents in relation to sexual violence, it is necessary to proffer a solution that collectively solves child and adolescent sexual abuse with all these identified factors. Future studies that will use the same approach but focus on the perceptions of other groups of individuals in the same community such as parents/guardians of child victims, convicted perpetrators and/or sexual victims are highly recommended.